Theoretical investigation of the charge-transfer properties in different meso-linked zinc porphyrins for highly efficient dye-sensitized solar cells - Namuangruk S. (Royal Society of Chemistry, 2014)
The charge transfer effect of different meso-substituted linkages on porphyrin analogue 1 (A1, B1 and C1) was theoretically investigated using density functional theory (DFT) and time-dependent DFT (TDDFT) calculations. The calculated geometry parameters and natural bond orbital analysis reveal that the twisted conformation between porphyrin macrocycle and meso-substituted linkages leads to blocking of the conjugation of the conjugated backbone, and the frontier molecular orbital plot shows that the intramolecular charge transfer of A1, B1 and C1 hardly takes place. In an attempt to improve the photoinduced intramolecular charge transfer ability of the meso-linked zinc porphyrin sensitizer, a strong electron-withdrawing group (CN) was introduced into the anchoring group of analogue 1 forming analogue 2 (A2, B2 and C2). The density difference plot of A2, B2 and C2 shows that the charge transfer properties dramatically improved. The electron injection process has been performed using TDDFT; the direct charge-transfer transition in the A2-(TiO 2)38 interacting system takes place; our results strongly indicated that introducing electron-withdrawing groups into the acceptor part of porphyrin dyes can fine-tune the effective conjugation length of the π-spacer and improve intramolecular charge transfer properties, consequently inducing the electron injection process from the anchoring group of the porphyrin dye to the (TiO2)38 surface which may improve the conversion efficiency of the DSSCs. Our calculated results can provide valuable information and a promising outlook for computation-aided sensitizer design with anticipated good properties in further experimental synthesis. © the Partner Organisations 2014.